Citizen Charter Model on Population and Civil Registration Services in Merauke Regency - Fransiskus E.S Kamijai (LEGAL BRIEF, 2022)
The Citizen Charter is a new approach model in public services that place service users as the center of attention or the most important element. In essence, a Resident contract is needed to provide service certainty which includes time, costs, procedures, and service methods, and to provide information on the rights and obligations of service users, service providers, and other partners in the overall expositions of service delivery . Thus, it can make it easier for service users, residents, and other partners to control service delivery practices and make it easier for service management to improve service delivery performance. This study aims to explain the citizen charter model in population services in Merauke Regency by referring to the citizen charter elements. This study uses a descriptive qualitative approach. Data was collected through interviews, observation, and documentation studies. Data processing and analysis techniques were carried out by data reduction, data display, and conclusion drawing/verification. Determination of informants using a purposive sampling technique. The results of the study show that the Citizen Charter model for Population Services in Merauke Regency, in general, has fulfilled the elements contained in the service contract which are: 1) Implementation of the service vision and mission; 2) There are service standards that serve as guidelines; 3) There is a service flow that is used as a service direction or guide; 4) Units or sections of complaints that do not specifically exist but in practice all existing units can carry out these functions.